The impact of nutritional status and dietary intake on children's exposure to hazardous substances in food - Wahyu Indah Dewi Aurora; Armaidi Darmawan; Erny Kusdiyah; Raihanah Suzan; Ahmad Syauqy; Patrick William Gading (Jurnal Gizi Indonesia: The Indonesian Journal of Nutrition, 2025)
Introduction: Exposure to harmful substances in food is a significant factor contributing to stunting and nutritional problems in children, as it impacts their growth and development. While healthy diets are well-documented, direct links between dietary intake and harmful substance exposure are less explored. This study investigates key risk factors influencing such exposure in children.